Plan de marketing para la reactivación hotelera de Manta, Portoviejo y Pedernales, afectados por el terremoto del 16 de abril en Manabí - Guzmán Moreira, José Damián (2019)
This research was carried out to design a marketing plan for the hotel sector in the province of Manabí that was most affected by the earthquake on April 16, 2016. For this end, information on the generalities of the province was raised. Then, the accommodation supply was analyzed in an ex ante- and ex post- earthquake to find out the number of hotels affected by the incident, with the information raised, it was able to characterize the current hotels of the cantons identified as the most affected (Manta, Portoviejo and Pedernales). The SWOT matrix was developed as of the information studied previously in the analysis, here, the strengths, opportunities, weaknesses and threats of the current hotels in Manabí were identified. On the other hand, the study of the demand was necessary to learn the profile of the tourist who currently visits the province and the one that existed before the earthquake; 384 surveys were applied to the managers and / or owners of the 5 and 4-star hotels of Manta, Portoviejo and Pedernales. The competitive profile matrix reported that the province of Santa Elena is the direct competition. The marketing plan was raised taking as reference the marketing mix of Kotler 2011, structuring the objectives, mission, vision, values and 16 medium-term projects were prepared with budget and execution plan, the brand is proposed for the hotel sector with the most relevant factors for its dissemination.